Efficacy and safety of TACE/HAIC combined with targeted immunotherapy versus targeted immunotherapy for advanced hepatocellular carcinoma: a meta-analysis - Liao, Yuting; Zhu, Wenliang; Zhang, Jianquan (Frontiers in Oncology, 2025)
IntroductionThe purpose of this study was to investigate the efficacy and safety of triple therapy with transcatheter arterial chemoembolization (TACE)/hepatic arterial infusion chemotherapy (HAIC) in patients with advanced hepatocellular carcinoma (HCC).MethodsA systematic literature search of multiple databases ending with publications from May 2024 was conducted. Interventions with TACE/HAIC combined with targeted immunotherapy versus targeted immunotherapy and patients with advanced HCC were included in this meta-analysis. Data from the 13 included studies, encompassing 2, 662 patients with HCC, were pooled using fixed- or random-effects models. The results are reported as hazard ratios (HRs) or risk ratios (RRs) with corresponding 95% confidence intervals (CIs).ResultsIn contrast to targeted immunotherapy, TACE/HAIC combined targeted immunotherapy can significantly improve overall survival (OS), progression-free survival (PFS) the disease control rate (DCR), and the objective response rate (ORR) in patients with advanced HCC. At the same time, the overall incidence of treatment-related adverse events (AEs) and treatment-related AEs of grade 3 or greater also increased, but only a few of the specific treatment-related AEs increased.ConclusionsGiven that combined TACE/HAIC with targeted immunotherapy significantly improves patient OS, PFS, DCR, and ORR, it may become standard for the treatment of patients with advanced HCC.